Numerical simulation for thermal flow filling process of casting - 陈晔 赵宇宏 侯华 (Transactions of Nonferrous Metals Society of China, 2006)
The solution algorithm （SOLA） method was used to solve the velocity and pressure field of the thermal flow filling process, and the volume of fluid （VOF） method for the flee surface problem. Since the ＂donor-acceptor＂ rule often results in the free interface vague, the explicit difference method was adopted, and a method describing the flee surface state at 0〈F〈 1 was proposed to deal with this problem. In order to raise the computation efficiency, such algorithms were investigated and invalidated as： 1） internal and external area separation simplification algorithm; 2） the reducing necessary search area method. With the improved algorithms, the filling processes of the valve cover castings with gravity cast and an up cylinder block casting with low-pressure cast were simulated, the simulation results are believable and the computation efficiency is greatly improved. The SOLA-VOF model and its difference method for thermal fluid flow filling process were introduced.